Studies in Isaiah - Jennings, Frederick Charles, 1847-1948 (New York, NY Loizeaux Brothers)
Includes bibliographical references and indexes.
Brethren writer. Third reprint, 1950.
Keywords: Bible. O.T. Isaiah -- commentaries